Unhardened body including hydraulic composition and fiber structure, hardened body of unhardened body, and fiber structure
By using a fiber structure with polymerizable silane compounds attached to the cement composition, the problems of poor fluidity and uneven impregnation are solved, and uniform distribution and fluidity maintenance of waterproof and corrosion resistance are achieved.
Patent Information
- Application Number
- JP2024115843
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-28
- Filing Date
- 2024-07-19
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, cement compositions containing silane compounds have poor fluidity during use, and are prone to uneven impregnation or insufficient corrosion resistance in inorganic building materials.
An uncured body comprises a cement composition and a fiber structure in which a polymerizable silane compound is attached to the fiber structure, and by controlling the release and distribution of the silane compound, it ensures that it is uniformly diffused in the cement composition and forms a waterproof, corrosion-proof film.
Effective waterproofing and corrosion-proofing effects in cement compositions are achieved, while maintaining good fluidity and uniformity, and improving the durability of building materials.
Smart Images

Figure 2025020022000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an uncured body containing a hydraulic composition and a fiber structure, a cured body of the uncured body, and a fiber structure. [Background technology]
[0002] Silane compounds are known to be agents that exhibit high water repellency, hydrophobicity, and / or rust prevention effects even in harsh environments. It is also known that silane compounds can be used in structures made of inorganic or organic building materials to impart water repellency, hydrophobicity, and / or rust prevention properties.
[0003] For example, Patent Document 1 describes a method for producing a polysiloxane comprising the steps of: (A) at least one organosiloxane; (B) at least one emulsifier; and (C) water, wherein the organosiloxane (A) is a C2-C6 alkyl group having a SiC bond and a C7-C8 alkyl group having a SiC bond. 18 and a) at least one hydraulic binder, preferably cement, b) at least one of the compositions, c) at least one aggregate, preferably selected from the group consisting of sand, gravel, limestone and chalk, and d) preferably additional water. The document discloses that the hydraulic composition is provided with a composition containing organosiloxane (A), so that the set body of the hydraulic composition is hydrophobized.
[0004] Patent Document 2 discloses that inorganic building materials such as concrete can be rendered hydrophobic by impregnating the materials with an n-propylethoxysiloxane oligomer mixture containing 80 to 100 mass % of n-propylethoxysiloxane having an oligomerization degree of 2 to 6.
[0005] In addition, in order to delay or prevent the corrosion of reinforcing bars in concrete structures, the use of corrosion inhibitors such as nitrite-based or amine-based inhibitors other than silane compounds has also been considered. For example, Patent Document 3 discloses a method for producing synthetic fibers for concrete with corrosion prevention function, which includes: 1) homogeneously mixing a solid gas-phase corrosion inhibitor mixture, blending and granulating the mixture with a polymer to obtain a polymer master batch for spinning; 2) mixing the polymer master batch obtained in step 1) with a new polymer material to which no solid gas-phase corrosion inhibitor has been added, and spinning a fiber precursor according to a conventional spinning process; 3) subjecting the fiber precursor obtained in step 2) to a short fiber post-spinning process (stirring, mixing and emulsifying the liquid gas-phase corrosion inhibitor in a conventional spinning oil to generate a stable post-spinning oil in an oil bath, and coating the fiber with the post-spinning oil); and 4) subjecting the synthetic fibers coated with the post-spinning oil to the steps of drawing, heat setting, cutting and packaging according to a conventional process. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2022 / 128994 [Patent Document 2] JP 2002-226490 A [Patent Document 3] China Patent Publication No. 101337782 Summary of the Invention [Problem to be solved by the invention]
[0007] However, according to the study by the present inventors, when a silane compound-containing composition or cut synthetic fiber kneaded and coated with a corrosion inhibitor is blended into a hydraulic composition as in Patent Document 1 and Patent Document 3, in order for the set body of the hydraulic composition to exhibit sufficient water repellency, hydrophobicity and / or rust prevention effects, a considerable amount of silane compound-containing composition or cut synthetic fiber must be blended, which adversely affects the fluidity of the hydraulic composition. Also, when a silane compound-containing composition is impregnated into an inorganic building material as in Patent Document 2, uneven impregnation or non-uniform impregnation may occur, which may lead to insufficient water repellency, hydrophobicity and / or rust prevention effects in the inorganic building material.
[0008] In view of the above, the problem to be solved by the present invention is to provide an uncured body containing a hydraulic composition and a fiber structure, which results in a cured body that exhibits water repellency, hydrophobicity and / or rust prevention effects. [Means for solving the problem]
[0009] In order to solve the above problems, the present inventors have conducted detailed studies on an uncured body containing a hydraulic composition and a fiber structure, and have completed the present invention. That is, the present invention includes the following preferred embodiments. [1] An uncured body comprising a hydraulic composition containing cement and a fiber structure having a composition containing a silane compound attached thereto, the fiber structure being embedded in the hydraulic composition. [2] The uncured body according to [1], wherein the silane compound contains a polymerizable silane compound. [3] The uncured material according to [1] or [2], wherein the silane compound is one or more compounds selected from the group consisting of organosilanes and organosiloxanes. [4] The uncured material according to any one of [1] to [3], wherein the silane compound comprises a monomeric silane compound. [5] The uncured body according to any one of [1] to [4], wherein the amount of the silane compound per 100 g of cement within 10 mm of the fiber structure is greater than the amount of the silane compound per 100 g of cement in the entire uncured body. [6] The uncured material according to any one of [1] to [5], wherein the fibers constituting the fiber structure have no acidic or basic functional groups and have hydrophilic functional groups. [7] The uncured material according to any one of [1] to [6], wherein the fiber constituting the fiber structure is a polyvinyl alcohol fiber. [8] The uncured body according to any one of [1] to [7], further comprising a reinforcing bar, the fiber structure and the reinforcing bar being embedded in the hydraulic composition in the order of fiber structure, reinforcing bar from the surface of the uncured body toward the inside. [9] The uncured body according to [8], wherein the distance between the fiber structure and the reinforcing bar is 10 mm or less.
[10] The uncured body according to any one of [1] to [9], wherein the fiber structure is one or more selected from the group consisting of long fibers, woven fabrics, knitted fabrics, nonwoven fabrics, unidirectional fiber bundles, spun yarns, and braided cords.
[11] A cured product of the uncured product according to any one of [1] to
[10] .
[12] The cured body according to
[11] , which contains a polymeric silane compound.
[13] The hardened body according to
[11] or
[12] , wherein the silane compound has an alkyl group, and the amount of hydrocarbons derived from the alkyl group released from the silane compound contained in the hardened body, detected when a cut piece of the hardened body within 10 mm of the fiber structure cut from the hardened body is subjected to pyrolysis-gas chromatography-mass spectrometry, per 100 g of cement contained in the cut piece of the hardened body is greater than the amount of hydrocarbons derived from the alkyl group released from the silane compound contained in the hardened body, detected when a hardened body of a hydraulic composition comprising cement and 0.5 parts by mass of the silane compound per 100 parts by mass of the cement is subjected to pyrolysis-gas chromatography-mass spectrometry, per 100 g of cement contained in the hardened body.
[14] A fiber structure having a composition containing a silane compound adhered thereto, the amount of the composition being 10 to 300 parts by mass per 100 parts by mass of the fiber structure to which the composition is not adhered.
[15] The fiber structure according to
[14] , wherein the silane compound includes a polymerizable silane compound.
[16] The fiber structure according to
[14] or
[15] , wherein the silane compound is one or more compounds selected from the group consisting of organosilanes and organosiloxanes.
[17] The fiber structure according to any one of
[14] to
[16] , wherein the silane compound comprises a monomeric silane compound.
[18] The fiber structure according to any one of
[14] to
[17] , wherein the fibers constituting the fiber structure have no acidic or basic functional groups and have hydrophilic functional groups.
[19] The fiber structure according to any one of
[14] to
[18] , wherein the fiber constituting the fiber structure is a polyvinyl alcohol fiber.
[20] The fiber structure according to any one of
[14] to
[19] , which is one or more selected from the group consisting of long fibers, woven fabrics, knitted fabrics, nonwoven fabrics, unidirectional fiber bundles, spun yarns, and braided cords.
[21] The formula: Silane compound release amount [mass parts] = Adhesion amount of silane compound-containing composition before cleaning [parts by mass] - Adhesion amount of silane compound-containing composition after cleaning [parts by mass] [In the formula, the adhesion amount of the silane compound-containing composition is the ratio of the mass of the silane compound-containing composition adhered to the fiber structure to 100 parts by mass of the fiber structure to which the silane compound-containing composition is not adhered] The fiber structure according to any one of
[14] to
[20] , wherein the amount of released silane compound represented by the formula: is 3 parts by mass or more. Effect of the Invention
[0010] According to the present invention, it is possible to provide an uncured body containing a hydraulic composition and a fiber structure, which gives rise to a cured body that exhibits water repellency, hydrophobicity and / or rust prevention effects. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view of one embodiment of the uncured body of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0013] [Uncured body] The uncured body of the present invention comprises a hydraulic composition containing cement (sometimes referred to in the present specification as a "cement-containing hydraulic composition") and a fiber structure having a composition containing a silane compound (sometimes referred to in the present specification as a "silane compound-containing composition") attached thereto, and in the uncured body, the fiber structure is embedded in the hydraulic composition. In this specification, the term "uncured body" refers to a stage where a fiber structure is embedded in a hydraulic composition, or a stage where the hydraulic composition in which the fiber structure is embedded has progressed to a certain degree but has not yet completed hardening. When this uncured body is left to stand for a long period of time or otherwise undergoes a known process to complete hardening, it becomes a hardened body. As used herein, "embedded" means that the fibrous structure is surrounded by the hydraulic composition, and therefore all of the fibrous structure is present in a state that it is contained in the uncured body and is not exposed from the uncured body.
[0014] <Hydraulic composition> The hydraulic composition contains cement. The cement is not particularly limited, and any cement specified in JIS R 5210:2019 to JIS R 5214:2019 can be used. Examples of the cement include ordinary Portland cement, high-early-strength Portland cement, ultra-high-early-strength Portland cement, and moderate-heat Portland cement; alumina cement; blast-furnace cement; silica cement; and fly ash cement; and white Portland cement. These cements may be used alone or in combination of two or more.
[0015] The above-mentioned cements are commercially available from, for example, Taiheiyo Cement Corporation, Sumitomo Osaka Cement Co., Ltd., UBE Mitsubishi Cement Corporation, etc., and such commercially available products can be used in the present invention.
[0016] The hydraulic composition usually further contains water. The amount of water in the hydraulic composition can be adjusted by a known blending amount according to the desired hardened product. When the mass of water is W and the mass of cement is C, the water-cement ratio (W / C) is preferably 25-65 mass%, more preferably 35-60 mass%, and even more preferably 40-55 mass%.
[0017] The hydraulic composition may further include aggregates known in the art. Examples of such aggregates include lightweight concrete aggregates specified in JIS A5002:2003, crushed stone and crushed sand specified in JIS A 5005:2020, slag aggregates specified in JIS A 5011-1:2018 to JIS A 5011-4:2018, and recycled aggregate H specified in JIS A 5021:2018. These aggregates may be used alone or in combination of two or more.
[0018] The hydraulic composition may further include an admixture and / or a chemical admixture. Examples of the admixture include fly ash as specified in JIS A 6201:2015, expansive material as specified in JIS A 6202:2017, ground granulated blast furnace slag as specified in JIS A 6206:2013, silica fume as specified in JIS A 6207:2016, and synthetic short fiber as specified in JIS A 6208:2018. Examples of the chemical admixture include chemical admixtures as specified in JIS A 6204:2011. These admixtures or chemical admixtures may be used alone or in combination of two or more.
[0019] When the hydraulic composition contains aggregates, admixtures and / or additives, they may be contained in the ranges generally used.
[0020] <Method for preparing hydraulic composition> The method for preparing the hydraulic composition is not particularly limited. Cement, water, and optionally the above-mentioned well-known aggregate, admixture and / or admixture are mixed uniformly. All materials may be mixed at the same time, or some materials may be mixed, and then the remaining materials may be added and further mixed.
[0021] As the stirring device, a known device can be used, and the stirring conditions may be appropriately set. Examples of the stirring device include a dissolver, a screw line mixer, an ultrasonic homogenizer, a colloid mill, a planetary mixer, a static mixer, a Nauta mixer, a ribbon blender, a tumble mixer, and a paddle mixer.
[0022] <Composition containing silane compound> The silane compound is a compound having a silane group in the molecule. The silane compound preferably includes a polymerizable silane compound, and more preferably consists of a polymerizable silane compound. The polymerizable silane compound is a silane compound having two or more polymerizable groups. The polymerizable group is preferably a hydrolytically polymerizable group, and examples thereof include alkoxy groups having 1 to 10 carbon atoms, such as a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a pentyloxy group, and a hexyloxy group. The hydrolytically polymerizable group is preferably an alkoxy group having 1 to 4 carbon atoms, and more preferably a methoxy group, an ethoxy group, and a propoxy group. The two or more polymerizable groups contained in the polymerizable silane compound may be the same group or different groups.
[0023] A composition containing a silane compound is attached to the fiber structure in the present invention. The term "attached" refers to a state in which the silane compound-containing composition covers at least a part of the surface of the fiber structure and / or is present in at least a part of the gaps of the fiber structure (the surface of the fibers constituting the fiber structure, or the surface and the inside), and refers to a state in which the silane compound can be separated (released) from the fiber structure in the presence of water, for example, in a hydraulic composition, in order to achieve the effects of the present invention. That is, the state in which the silane compound-containing composition is "attached" to the fiber structure does not include a state in which the silane compound-containing composition is fixed or set to the fiber structure by high temperature, pH conditions, etc. The silane compound fixed or set to the fiber structure is not released from the fiber structure in the presence of water, and therefore, even if such a fiber structure is embedded in a hydraulic composition, the effects of the present invention cannot be obtained. The silane compound released from the fibrous structure in the presence of water includes a polymerizable silane compound or a non-polymeric silane compound, and preferably consists of a polymerizable silane compound or a non-polymeric silane compound. On the other hand, the fixed or set silane compound-containing composition usually contains a polymeric silane compound as the silane compound. Therefore, even if the silane compound falls off from the fiber structure due to a physical action or the like in water or in a hydraulic composition, the fallen silane compound will not hydrolyze or polymerize to form a water-repellent film or the like described later.
[0024] The silane compound released from the fiber structure in the hydraulic composition diffuses to the vicinity of the fiber structure, where it is hydrolyzed and polymerized, and the polymer silane compound is considered to be generated as something like a water-repellent film (hereinafter, sometimes referred to as a "film-like substance"). As a result, the polymer silane compound is present (locally) in a higher concentration in the vicinity of the fiber structure in the hardened body than in other places, and the hardened body is considered to be able to exhibit water-repellent, hydrophobic and / or rust-preventive effects against moisture from the outside. Due to this local presence, it is considered that sufficient water-repellent, hydrophobic and / or rust-preventive effects are exhibited even if the amount of the silane compound is significantly less than when the silane compound-containing composition or cut fibers kneaded or coated with the silane compound-containing composition are blended in the entire hardened body. In addition, unlike when the silane compound-containing composition or cut fibers kneaded or coated with the silane compound-containing composition are blended in the entire hardened body, the fluidity of the hydraulic composition is not adversely affected. Furthermore, by positioning the fiber structure to which the silane compound-containing composition is attached at an appropriate position in the hydraulic composition, a film-like material can be formed that is free of uneven or non-uniform distribution of the silane compound, which would result in insufficient water repellency, hydrophobicity and / or rust prevention effects.
[0025] The silane compound preferably comprises a monomeric silane compound and / or an oligomeric silane compound (collectively sometimes referred to herein as "non-polymeric silane compound"), and more preferably comprises a non-polymeric silane compound. The silane compound preferably comprises a monomeric silane compound. The silane compound may also comprise a polymeric silane compound.
[0026] The non-polymeric silane compound attached to the fiber structure is easily discharged from the fiber structure in the presence of water (e.g., by washing with water). On the other hand, the polymeric silane compound that can be attached to the fiber structure is not discharged from the fiber structure in the presence of water (it is possible that a part of the polymeric silane compound falls off from the fiber structure, for example, by washing with water). Therefore, when the uncured body includes a fiber structure to which a composition containing a silane compound including a non-polymeric silane compound is attached, the non-polymeric silane compound is easily released from the fiber structure. The proportion of non-polymeric silane compounds and, if present, polymeric silane compounds in the silane compounds attached to the fiber structure can be adjusted, for example, by the temperature or time in the heat treatment process for attaching the silane compounds to the fiber structure, and / or the material of the fibers constituting the fiber structure or the type of components applied, attached or coated on the fiber surface. The proportion of non-polymeric silane compounds and, if present, polymeric silane compounds in the silane compounds attached to a fiber structure can be measured, for example, by the mass of the fiber structure to which no silane compound is attached, the mass after the silane compound has been attached to the fiber structure, and the change in the mass of the silane compound after the fiber structure has been washed with water after the attachment.
[0027] In one embodiment, the silane compound is one or more compounds selected from the group consisting of organosilanes and organosiloxanes. The organosilanes preferably include alkylalkoxysilanes and aminosilanes. The organosilanes and organosiloxanes may be used alone or in combination.
[0028] Examples of alkylalkoxysilanes include methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, heptyltrimethoxysilane, heptyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, nonyltrimethoxysilane, nonyltriethoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, cyclohexyltriethoxysilane, cyclohexyltributoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, and methyloctyldimethoxysilane, methyloctyldiethoxysilane.
[0029] Examples of aminosilanes include aminopropyltrimethoxysilane, aminopropyltriethoxysilane, aminobutyltrimethoxysilane, aminobutyltriethoxysilane, aminopropylmethyldiethoxysilane, and n-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0030] Examples of the organosiloxane include the above-mentioned organosilane oligomers and polymers. From the viewpoint of good release properties from the fiber structure, the organosiloxane is preferably an organosilane oligomer.
[0031] The silane compound-containing composition may be a commercially available product. Examples of such commercially available products include Protectosil® WA CIT manufactured by Evonik Industries, Protectosil® WS670 manufactured by Evonik Industries, and Master Protect H400 manufactured by Pozzolith Solutions, Inc.
[0032] The silane compound-containing composition is preferably an emulsion. According to the study by the present inventors, it has been found that in an uncured body including a fibrous structure to which the silane compound itself is attached and a cement-containing hydraulic composition, the silane compound may not be released well from the fibrous structure in the cement-containing hydraulic composition. The reason is not clear, and it is not intended to be limited to the following reasons, but it is considered that when the silane compound itself is attached to the fibrous structure, the silane compound polymerizes on the surface or near the surface of the fibrous structure and cannot diffuse from the fibrous structure into the cement-containing hydraulic composition, whereas when a composition (preferably an emulsion) containing a silane compound is attached to the fibrous structure, the composition containing the silane compound does not polymerize or does not polymerize much on the surface or near the surface of the fibrous structure and can diffuse from the fibrous structure into the cement-containing hydraulic composition. When the silane compound-containing composition is an emulsion, it is considered that the non-polymer silane compound present in the oil droplets of the emulsion is attached to the fibrous structure, so that the non-polymer silane compound can be released well into the cement-containing hydraulic composition and can diffuse near the fibrous structure.
[0033] The concentration of the silane compound in the silane compound-containing composition is preferably 10 to 90% by mass, more preferably 30 to 70% by mass, and even more preferably 40 to 60% by mass, based on the mass of the silane compound-containing composition. When the concentration of the silane compound in the silane compound-containing composition is within the above range, polymerization is unlikely to occur on the surface or in the vicinity of the surface of the fiber structure, and good release and diffusion of the non-polymeric silane compound into the cement-containing hydraulic composition can be achieved.
[0034] The silane compound-containing composition preferably contains an emulsifier. In particular, when the silane compound-containing composition is an emulsion, the silane compound-containing composition usually further contains an emulsifier in addition to the silane compound and water. Known emulsifiers can be used as such emulsifiers, and specific examples thereof include nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl allyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, glycerin fatty acid esters, polyoxyethylene fatty acid esters, dimethylsiloxane copolymers in which the side chain or end of dimethylsiloxane is modified with polyalkylene oxide, and cellulose; anionic emulsifiers such as alkylbenzene sulfonates, higher alcohol sulfates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkyl phenyl ether sulfates, and alkyl naphthyl salts; and cationic emulsifiers such as alkylamine salts and quaternary ammonium salts. These emulsifiers may be used alone or in combination of two or more.
[0035] The concentration of the emulsifier in the silane compound-containing composition as an emulsion may be appropriately selected and is usually 0.1% by mass to 20% by mass, preferably 0.5% by mass to 15% by mass, and more preferably 1.0% by mass to 10% by mass, relative to the mass of the emulsion.
[0036] The silane compound-containing composition may optionally contain additives known in the art. Examples of such additives include thickeners, pH buffers, pH adjusters, silica sols, alumina sols, ceria sols, UV absorbers, water-soluble polymers, organic emulsion polymers, antifungal agents, anti-algae agents, and anti-termite agents. These additives may be used alone or in combination of two or more, and the amount of use may be appropriately selected.
[0037] <Fiber structure and method for producing same> In a preferred embodiment, the fiber structure is one or more selected from the group consisting of long fibers, woven fabrics, knitted fabrics, nets, nets, nonwoven fabrics, unidirectional fiber bundles, spun yarns, ropes, and braided cords. As described above, the uncured body may contain synthetic staple fibers as necessary. However, the fiber structure does not include synthetic staple fibers. When the fiber structure is a long fiber, unidirectional fiber bundle, spun yarn, or braided cord, its longitudinal length is preferably 100 mm or more, more preferably 500 mm or more. Examples of woven fabrics include plain weave, twill weave, satin weave, triaxial weave, quadraxial weave, leno weave, and leno weave. Examples of knitted fabrics include tricot, raschel, and Milanese. Examples of nets include knotted nets such as main mesh nets, frog nets, and double frog nets, knotless nets such as raschel nets, leno nets, woven nets, and metric fiber nets. The mesh of the net can be in the shape of a diamond, a tortoiseshell, a square, a staggered pattern, a hexagon, etc. Among these nets, a knotless net having no knots and planar joints is preferred from the viewpoint of ease of handling and construction.
[0038] The shape and mesh size of woven fabrics, knitted fabrics and nonwoven fabrics, and the width of the gap or the size of the mesh when a specific shape (e.g., a shape arranged at intervals or a lattice shape) is formed from a plurality of long fibers to form a fiber structure, are appropriately determined depending on the application. Usually, the width of the gap or the size of the mesh size of woven fabrics, knitted fabrics and nonwoven fabrics, and the width of the gap or the size of the mesh when a specific shape is formed from a plurality of long fibers to form a fiber structure are 3 to 120 mm.
[0039] The average fiber diameter of the fibers constituting the fiber structure is preferably 1 to 50 μm, more preferably 2.5 to 45 μm, and even more preferably 5 to 40 μm. When the average fiber diameter is within the above range, the retention of the silane compound can be improved. The average fiber diameter can be determined in accordance with JIS L 1015 "Test method for chemical fiber staple (8.5.1)".
[0040] The average diameter of the braided cord is preferably 0.5 to 10 mm, more preferably 1 to 7 mm, and even more preferably 1.5 to 5 mm. When the average diameter is within the above range, the retention of the silane compound is improved and the handling during application is improved. The average diameter can be determined by measuring the diameter at any multiple points (for example, 10 points) using a scanning electron microscope or an optical microscope and calculating the average value.
[0041] In a preferred embodiment, the fibers constituting the fiber structure are organic fibers or inorganic fibers. Examples of the organic fibers include polyvinyl alcohol fibers, aramid fibers, polypropylene fibers, cellulose fibers, polyester fibers, etc., and examples of the inorganic fibers include glass fibers, carbon fibers, etc. When it is desired to impart a reinforcing effect and a crack suppression effect, fibers that have high strength and do not lose strength in the presence of alkali, such as polyvinyl alcohol fibers, aramid fibers, polypropylene fibers, glass fibers, and carbon fibers, can be suitably used.
[0042] In another preferred embodiment, the fibers constituting the fiber structure have no acidic or basic functional groups, but have hydrophilic functional groups. Since the fibers do not have acidic or basic functional groups, polymerization of the silane compound is unlikely to occur on the fiber surface or in the vicinity of the surface, and good release and diffusion of the non-polymeric silane compound into the cement-containing hydraulic composition can be achieved. Furthermore, since the fibers have hydrophilic functional groups, a sufficient amount of the silane compound-containing composition can be attached to the fiber structure, and a sufficient amount of the non-polymeric silane compound can be released and diffused into the cement-containing hydraulic composition. That is, fibers that do not have acidic or basic functional groups and have hydrophilic functional groups can have both the ability to retain a large amount of the silane compound as a non-polymeric silane compound and the ability to release a large amount of the non-polymeric silane compound.
[0043] The fiber structure may be composed of a combination of two or more fibers that differ in one or more of the average fiber diameter, composition, and saponification degree of the polyvinyl alcohol fiber described below, or may be composed of only the same fibers.
[0044] An example of a fiber having a hydrophilic functional group but no acidic or basic functional group is polyvinyl alcohol fiber.
[0045] The polyvinyl alcohol fiber is a fiber containing a vinyl alcohol-based polymer. From the viewpoints of mechanical strength, alkali resistance, hydrophilicity, and the like, the content of the vinyl alcohol-based polymer in the polyvinyl alcohol fiber is preferably 30% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, still more preferably 90% by mass or more, and particularly preferably 100% by mass.
[0046] The polyvinyl alcohol fiber may be a composite fiber with other polymers or a sea-island fiber, so long as the effects of the present invention are not impaired. The vinyl alcohol-based polymer is mainly composed of polyvinyl alcohol, and may be copolymerized with other monomers than vinyl alcohol or may be modified, so long as the effects of the present invention are not impaired. From the viewpoints of the mechanical strength and alkali resistance of the fiber, the ratio of modified units in the vinyl alcohol-based polymer is preferably 30 mol % or less, more preferably 10 mol % or less. From the viewpoints of the mechanical strength and alkali resistance of the fiber, the average polymerization degree of the vinyl alcohol-based polymer determined by the viscosity method in an aqueous solution at 30°C is preferably 1000 or more, more preferably 1500 or more, and from the viewpoints of production costs, etc., it is preferably 10000 or less, more preferably 5000 or less, and even more preferably 3000 or less. From the viewpoints of heat resistance, durability, dimensional stability, and retention of non-polymeric silane compounds, the saponification degree is preferably 99 mol % or more, more preferably 99.8 mol % or more.
[0047] The polyvinyl alcohol fiber can be prepared, for example, by the following method. The vinyl alcohol-based polymer as described above is made into a water-containing chip shape with a concentration of 40 to 60% by mass, and is heated and dissolved in an extruder, followed by defoaming. Next, a crosslinking agent is added to this polyvinyl alcohol-based polymer aqueous solution to obtain a spinning dope. Examples of the crosslinking agent include ammonium sulfate, sulfuric acid, ammonium phosphate, phosphoric acid, hydrochloric acid, nitric acid, acetic acid, and oxalic acid. Ammonium sulfate is preferred from the viewpoint of not corroding piping, not giving off a foul odor, and not foaming the fibers. The amount of the crosslinking agent added is preferably 0.5 to 10% by mass relative to the mass of the polyvinyl alcohol-based polymer. The temperature of the spinning dope is preferably 90 to 140°C. Next, the spinning dope is pressurized and discharged from the nozzle hole into the air to perform dry spinning. The nozzle hole may be circular or may be of a different shape other than circular, such as a flat, cross, T-shaped, Y-shaped, L-shaped, triangular, rectangular, or star-shaped. The spinning method may be any of wet, dry-wet and dry methods.
[0048] Next, the polyvinyl alcohol fibers obtained by spinning are dried. The drying temperature is usually 100° C. or lower, and it is preferable to dry the fibers to a certain degree and then completely dry them at a temperature of 100° C. or higher.
[0049] After drying, the fibers are stretched. The stretching is usually performed at a temperature of 200 to 250°C, preferably 220 to 240°C. The stretching ratio is usually 5 times or more, preferably 6 times or more. During stretching, the crosslinking agent added to the spinning dope reacts with the OH group of the polyvinyl alcohol to generate crosslinks. The stretching is performed in a hot air stretching furnace for about 20 seconds to 3 minutes. The fibers thus stretched are heat-treated as necessary to achieve a fixed length or shrinkage.
[0050] As the fibers constituting the fiber structure, commercially available fibers may be used. The method for producing a fiber structure from fibers is not particularly limited, and any known method can be used.
[0051] <Fiber structure having a composition containing a silane compound attached thereto and a method for producing the same> A silane compound-containing composition is attached to the fiber structure in the present invention. The amount of the attached silane compound-containing composition is preferably 10 to 300 parts by mass, more preferably 20 to 100 parts by mass, even more preferably 30 to 90 parts by mass, and particularly preferably 40 to 80 parts by mass, relative to 100 parts by mass of the fiber structure to which the silane compound-containing composition is not attached. When the amount of the attached silane compound-containing composition is within the above range, good release and diffusion of the non-polymer silane compound into the cement-containing hydraulic composition can be achieved. The amount of the attached silane compound-containing composition can be measured by the method described in the Examples below.
[0052] The formula: Silane compound release amount [mass parts] = Adhesion amount of silane compound-containing composition before cleaning [parts by mass] - Adhesion amount of silane compound-containing composition after cleaning [parts by mass] [In the formula, the adhesion amount of the silane compound-containing composition is the ratio of the mass of the silane compound-containing composition adhered to the fiber structure to 100 parts by mass of the fiber structure to which the silane compound-containing composition is not adhered] The amount of silane compound released from the fiber structure represented by is preferably 3 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, and particularly preferably 30 parts by mass or more. When the amount of silane compound released is equal to or more than the lower limit, the non-polymer silane compound can be released well from the fiber structure into the cement-containing hydraulic composition and can diffuse in the vicinity of the fiber structure. The amount of silane compound released can be adjusted to equal to or more than the lower limit by appropriately selecting the above-mentioned silane compound, silane compound-containing composition, and fiber structure, particularly the silane compound, silane compound-containing composition, and fiber structure described as preferred embodiments. The upper limit of the amount of silane compound released is not particularly limited and may be 100 parts by mass. The amount of silane compound released can be measured by the method described in the Examples below.
[0053] The fiber structure having the composition containing a silane compound attached thereto can be produced, for example, by impregnating the fiber structure with the composition containing a silane compound using a general method such as immersion, spraying, or coating, and squeezing and / or drying as necessary. In addition, when the fiber structure is a woven fabric, knitted fabric, nonwoven fabric, unidirectional fiber bundle, or braided cord, the fiber structure may be produced using fibers that have been impregnated with the composition containing a silane compound and, as necessary, squeezed and / or dried.
[0054] The concentration of the silane compound in the silane compound-containing composition to be contained in the fiber structure or fibers is preferably 10 to 90 mass %, more preferably 30 to 70 mass %, and even more preferably 40 to 60 mass %, relative to the mass of the silane compound-containing composition.
[0055] The silane compound that can be blended in the silane compound-containing composition is the silane compound described in the above section <Composition containing a silane compound>. The silane compound-containing composition is preferably an emulsion. When the silane compound-containing composition is an emulsion, the emulsifier that is usually contained and the conventionally known additive that can be optionally contained are the emulsifier and additive described in the above section <Composition containing a silane compound>.
[0056] When the silane compound-containing composition is an emulsion, a general mixing / emulsifying method can be used to prepare the emulsion. For example, the emulsion can be prepared by adding a silane compound, usually an emulsifier, and optionally an additive, separately or in advance, to water little by little or all at once while stirring using a stirrer, homomixer, ultra disperser, high-pressure homogenizer, etc., or by adding a silane compound little by little or all at once to a mixture of water, usually an emulsifier, and optionally an additive.
[0057] The fiber structure or fiber impregnated with the silane compound-containing composition is subjected to squeezing and / or drying as necessary. Squeezing and drying can be performed by a general method, and the temperature at that time is preferably less than 130°C, more preferably 100°C or less, even more preferably 80°C or less, and particularly preferably 60°C or less, from the viewpoint of preventing the silane compound-containing composition from being fixed or set on the fiber structure or fiber. In addition, reduced pressure may be applied during drying.
[0058] In a preferred embodiment of the uncured body, the amount of the silane compound per 100 g of cement within a range of 10 mm from the fiber structure is greater than the amount of the silane compound per 100 g of cement in the entire uncured body. Here, the "range of 10 mm from the fiber structure" described in this specification does not include the fiber structure and anything attached or set on the surface of the fiber structure or fiber. In other words, the range of 10 mm from the fiber structure means a range of more than 0 mm to 10 mm from the fiber structure. In addition, the volume of the uncured body within a range of 10 mm from the fiber structure is smaller than the volume of the entire uncured body.
[0059] A preferred embodiment of the uncured body described above shows that the silane compound released from the fiber structure is locally present in a large amount in the hydraulic composition near the fiber structure in the uncured body (specifically, in the hydraulic composition within 10 mm from the fiber structure). Therefore, if the amount of the silane compound within 10 mm from the fiber structure is greater than the amount of the silane compound per 100 g of cement in the entire uncured body, the silane compound can be unevenly distributed in the uncured body as desired. Due to this uneven distribution, even if the amount of the silane compound is significantly less than when the silane compound-containing composition or cut fibers kneaded or coated with the silane compound-containing composition are mixed in the entire cured body, sufficient water repellency, hydrophobicity and / or rust prevention effects can be exhibited in the cured body. Such uneven distribution of the silane compound can be achieved by producing an uncured body using the above-mentioned silane compound, silane compound-containing composition, and fiber structure, in particular, by producing an uncured body using the silane compound, silane compound-containing composition, and fiber structure described as preferred embodiments.
[0060] The amount of the silane compound per 100 g of cement in a specific region of the uncured body or in the entire uncured body can be measured by, for example, pyrolysis gas chromatography. Here, the amount of the silane compound or the amount of the alkyl group (hereinafter, sometimes referred to as "silane compound-derived alkyl group") when the silane compound has an alkyl group does not change substantially due to the curing of the hydraulic composition. Therefore, the amount of the silane compound or the alkyl group derived from the silane compound in the entire uncured body can be considered to be equivalent to the amount of the silane compound or the alkyl group derived from the silane compound in the entire cured body obtained by curing the uncured body. In addition, the amount of the silane compound or the alkyl group derived from the silane compound in a specific region of the uncured body can be considered to be equivalent to the amount of the silane compound or the alkyl group derived from the silane compound in a cured body obtained by cutting out the uncured body in the specific region and curing it. Furthermore, the amount of the silane compound or the alkyl group derived from the silane compound in a specific region of the uncured body that has been cured to a certain extent can be considered to be equivalent to the amount of the silane compound or the alkyl group derived from the silane compound in the specific region of the cured body obtained by curing the uncured body. A specific example of the measurement method using pyrolysis gas chromatography will be described in the Examples section below.
[0061] When examining the amount of silane compounds or alkyl groups derived from silane compounds in a range of 10 mm or less from a fiber structure in an uncured body, for example, in the case of a woven fabric in which the fiber structure is arranged horizontally with the bottom surface of the uncured body, the amount of silane compounds or alkyl groups derived from silane compounds in a range of 10 mm below and 10 mm above the fiber structure is examined. However, in an uncured body, the silane compounds released from the fiber structure can usually be released in any direction, not in a specific direction. In this case, the amount of silane compounds or alkyl groups derived from silane compounds in a range of 10 mm below the fabric and the amount of silane compounds or alkyl groups derived from silane compounds in a range of 10 mm above the fabric can be substantially the same. In such a case, the amount of silane compounds or alkyl groups derived from silane compounds in a range of 10 mm below the fabric or the amount of silane compounds or alkyl groups derived from silane compounds in a range of 10 mm above the fabric can be examined, and the amount can be simply regarded as the amount of silane compounds or alkyl groups derived from silane compounds in a range of 10 mm or less from a fiber structure.
[0062] In one embodiment of the present invention, the uncured body further includes a reinforcing bar, and the reinforcing bar and the fiber structure are embedded in the hydraulic composition in the order of the fiber structure and the reinforcing bar from the surface of the uncured body toward the inside. Here, the "surface of the uncured body" means the interface between the uncured body and another phase (typically, the formwork in which the uncured body is contained, or the atmosphere). The "inside" of the uncured body means the inside of the surface of the uncured body, i.e., the opposite side to the other phase, and the "outside" of the uncured body means the outside of the surface of the uncured body, i.e., the other phase side. The same applies to the surface, inside, and outside of the cured body.
[0063] In the uncured body, the silane compound released from the fiber structure diffuses into the hydraulic composition and is hydrolyzed and polymerized near the fiber structure, and the polymerized silane compound can preferably exist as a film-like substance. By having the fiber structure and the reinforcing bar present in this order from the surface of the uncured body toward the inside, in the hardened body of the uncured body, moisture from the outside of the hardened body can reach the film-like substance before the reinforcing bar and be blocked by the film-like substance. This can prevent moisture from reaching the reinforcing bar present inside (inside) the film-like substance, and can achieve rust prevention of the reinforcing bar.
[0064] Fig. 1 shows a schematic cross-sectional view of an uncured body (1) according to one embodiment of the present invention. As shown in the schematic cross-sectional view, a plurality of reinforcing bars (4) are present inside a fiber structure (3) to which a silane compound-containing composition is attached, and the fiber structure (3) and the reinforcing bars (4) are surrounded by a hydraulic composition (2). The polymeric silane compound produced by the diffusion of the silane compound released from the fiber structure into the hydraulic composition and hydrolysis and polymerization in the vicinity of the fiber structure can preferably exist as a film-like substance, but is not shown in Fig. 1. In Fig. 1, the dimensions and ratios of each component are appropriately changed to make the drawing easier to understand.
[0065] In one embodiment in which the uncured body further contains a reinforcing bar, the distance between the fiber structure and the reinforcing bar is preferably 10 mm or less, more preferably 5 mm or less, even more preferably 1 mm or less, and may be 0 mm. This distance is the distance between the reinforcing bar and the fiber structure closest to the reinforcing bar. When the distance between the fiber structure and the reinforcing bar is equal to or less than the upper limit, a film-like material of the polymerized silane compound can be present in the vicinity of the reinforcing bar, so that good rust prevention of the reinforcing bar can be achieved. The distance can be measured by cutting the uncured body after curing has progressed to such an extent that the shape of the uncured body is maintained even if the uncured body is cut, measuring the distance between the reinforcing bar and the fiber structure at one or more points (preferably three or more points) every 20 cm, and calculating the average value. Alternatively, since the distance between the fiber structure and the reinforcing bar does not substantially change due to the hardening of the hydraulic composition, as described in the examples below, a mortar piece near the reinforcing bar in the hardened body is split, and the distance between the reinforcing bar and the fiber structure is measured at one or more points (preferably three or more points) every 20 cm, the average value is calculated, and this value can be used as the distance between the fiber structure and the reinforcing bar in the unhardened body. Alternatively, an unhardened body in which a fiber structure and a reinforcing bar are embedded is usually produced by fixing the fiber structure and the reinforcing bar to a formwork and then casting a hydraulic composition into the formwork, and since the positions of the fiber structure and the reinforcing bar do not substantially change due to this casting, before casting the hydraulic composition, the distance between the fixed fiber structure and the reinforcing bar is measured at one or more points (preferably three or more points) every 20 cm, the average value is calculated, and this value can be used as the distance between the fiber structure and the reinforcing bar in the unhardened body.
[0066] [Method of manufacturing uncured body] The uncured body can usually be produced by a method including fixing the fiber structure to which the composition containing a silane compound is attached and the reinforcing bar, if included, in a formwork, and then pouring the hydraulic composition into the formwork. The method for fixing the fiber structure is not particularly limited as long as the fiber structure is fixed to the formwork and / or the reinforcing bar, if included, to an extent that it does not move due to the pouring of the hydraulic composition. For example, as illustrated in FIG. 1, when multiple reinforcing bars are embedded in the hydraulic composition, multiple reinforcing bars (4) are fixed to the formwork by a conventionally known method, and a woven fiber structure, for example, is wrapped around the reinforcing bars, and the ends of the fiber structure are joined together with a joining member such as a binding wire, thereby fixing the fiber structure.
[0067] [Hardened body and its manufacturing method] A cured body is obtained by curing the uncured body. The present invention also covers a cured body of such an uncured body.
[0068] In the uncured body, the silane compound released from the fiber structure diffuses into the hydraulic composition and undergoes hydrolysis and polymerization in the vicinity of the fiber structure. Thus, the cured body contains a polymeric silane compound. The inclusion of the polymeric silane compound produced by the hydrolysis and polymerization in the cured body allows the cured body to have sufficient water repellency, hydrophobicity and / or rust prevention against moisture from the outside. The inclusion of a polymeric silane compound in the cured body can be confirmed, for example, by the method described in the Examples below. The cured product may contain unreacted monomeric silane compounds in some cases, and may also contain unreacted oligomeric silane compounds and / or oligomeric silane compounds produced by hydrolysis and polymerization of monomeric silane compounds.
[0069] As described above, in the uncured body of the present invention, the silane compound is released from the fibrous structure and is unevenly distributed in the vicinity of the fibrous structure. Therefore, in the cured body of the present invention, the silane compound is unevenly distributed in the vicinity of the fibrous structure. In a preferred embodiment of the hardened body, the amount of the silane compound per 100 g of cement in a range within 10 mm from the fiber structure is greater than the amount of the silane compound per 100 g of cement in the entire hardened body.
[0070] In a preferred embodiment, the silane compound has an alkyl group, and the amount of hydrocarbons derived from the alkyl group released from the silane compound contained in the hardened body cut out from the hardened body cut out piece within 10 mm from the fiber structure, detected when the hardened body cut out piece is subjected to pyrolysis gas chromatography mass spectrometry, per 100 g of cement contained in the hardened body cut out piece is greater than the amount of hydrocarbons derived from the alkyl group released from the silane compound contained in the hardened body, detected when the hardened body of a hydraulic composition comprising cement and 0.5 parts by mass of the silane compound per 100 parts by mass of the cement is subjected to pyrolysis gas chromatography mass spectrometry, per 100 g of cement contained in the hardened body. A specific example of the pyrolysis gas chromatography mass spectrometry method is described in the Examples below. Since the amount of the alkyl group does not change upon curing, the amount of the above-mentioned hydrocarbons detected when a piece of the cured product cut out from the cured product is subjected to pyrolysis-gas chromatography-mass spectrometry is substantially the same as when a piece of an uncured product is cut out from the cured product, where curing has progressed to a certain extent and release of the silane compound from the fiber structure is thought to be complete, and the resulting cured product is then cured to obtain a cured product, and the amount of the above-mentioned hydrocarbons detected is substantially the same when the piece of the uncured product is cut out from the cured product and subjected to pyrolysis-gas chromatography-mass spectrometry is then subjected to pyrolysis-gas chromatography-mass spectrometry.
[0071] The uncured body may be cured by a general method depending on the application of the cured body.
[0072] [Fiber structure and method for producing same] The present invention also relates to a fiber structure having a composition containing a silane compound attached thereto, wherein the amount of the silane compound-containing composition is preferably 10 to 300 parts by mass per 100 parts by mass of the fiber structure to which the silane compound-containing composition is not attached.
[0073] In a preferred embodiment, the silane compound includes a polymerizable silane compound and also includes a monomeric silane compound. In a preferred embodiment, the silane compound is one or more compounds selected from the group consisting of organosilanes and organosiloxanes. In a preferred embodiment, the fibers constituting the fiber structure have no acidic or basic functional groups, but have hydrophilic functional groups, and are preferably polyvinyl alcohol fibers. The fiber structure is preferably one or more selected from the group consisting of long fibers, woven fabrics, knitted fabrics, nonwoven fabrics, unidirectional fiber bundles, spun yarns, and braided cords. In one preferred embodiment, the compound of the formula: Silane compound release amount [mass parts] = Adhesion amount of silane compound-containing composition before cleaning [parts by mass] - Adhesion amount of silane compound-containing composition after cleaning [parts by mass] [In the formula, the adhesion amount of the silane compound-containing composition is the ratio of the mass of the silane compound-containing composition adhered to the fiber structure to 100 parts by mass of the fiber structure to which the silane compound-containing composition is not adhered] The amount of the silane compound released from the fiber structure represented by the formula (I) is preferably 3 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, and particularly preferably 30 parts by mass or more. The upper limit of the amount of the silane compound released is not particularly limited, and may be 100 parts by mass.
[0074] With regard to the explanation related to the above-mentioned preferred embodiment of the fiber structure, a preferred embodiment or an embodiment other than the above-mentioned preferred embodiment of the fiber structure, and a method for producing a fiber structure and a preferred embodiment or an embodiment thereof, those described in the sections <Composition containing a silane compound>, <Fiber structure and method for producing the same>, and <Fiber structure having a composition containing a silane compound attached thereto and method for producing the same> can be applied.
[0075] The fiber structure to which the composition containing the silane compound of the present invention is attached can be suitably used as a material for imparting water repellency, hydrophobicity and / or rust prevention, a concrete reinforcing material, a crack repair material, etc. As the material for imparting water repellency, hydrophobicity and / or rust prevention, it can be used, for example, as a material to be buried in an uncured body of a hydraulic composition containing cement.
[0076] When a fiber structure having a composition containing the silane compound of the present invention attached thereto is embedded in an uncured body of a hydraulic composition containing cement, the resulting cured body can exhibit good water repellency, hydrophobicity and / or rust prevention effects. EXAMPLES
[0077] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The physical properties in the examples and comparative examples were measured or evaluated according to the following procedures.
[0078] <Amount of silane compound-containing composition attached to fiber structure> The fiber structure to which the silane compound-containing composition was not attached was dried at 80°C until it reached a constant weight, and then its mass (W0) was measured. The fiber structure was then immersed in an aqueous emulsion of the silane compound for 5 minutes, and then pulled out of the aqueous emulsion, squeezed, and dried at 80°C for 10 minutes, and its mass (W1) was measured. The amount of the silane compound-containing composition attached to the fiber structure relative to the mass (W0) of the fiber structure to which the silane compound-containing composition was not attached was calculated using the following formula (1). Amount of silane compound-containing composition attached to fiber structure relative to W0 [parts by mass] ={(W1-W0) / W0}×100 (1)
[0079] <Release of silane compounds from fiber structures> The amount of the silane compound-containing composition adhering to the fiber structure relative to W0 was determined in the same manner as above. This amount is referred to as the "adhering amount of the silane compound-containing composition before washing (rinsing with water)." Next, the fiber structure to which the silane compound-containing composition was attached was immersed in water for 240 minutes, then removed from the water and dried at 80°C for 10 minutes, and its mass (W2) was measured. The amount of the silane compound-containing composition attached to the fiber structure after washing (rinsing with water) relative to the mass (W0) of the fiber structure to which the silane compound-containing composition was not attached was calculated using the following formula (2). Amount of the silane compound-containing composition adhering to the fiber structure after washing relative to W0 [parts by mass] = {(W2-W0) / W0} x 100 (2) This amount is referred to as the "adhesion amount of the silane compound-containing composition after cleaning." By immersing the fiber structure in water as described above, at least a part of the silane compound attached to the fiber structure is released from the fiber structure into the water. Therefore, the difference between the "adhesion amount of the silane compound-containing composition before washing" calculated according to formula (1) and the "adhesion amount of the silane compound-containing composition after washing" calculated according to formula (2) corresponds to the amount of the silane compound released from the fiber structure into the water by washing with water, and is represented by the following formula (3). This was used as an index of the release of the silane compound from the fiber structure. The silane compound released from the fiber structure into the water is a non-polymer silane compound. Silane compound release amount [mass parts] = Adhesion amount of silane compound-containing composition before cleaning [parts by mass] - Adhesion amount of silane compound-containing composition after cleaning [parts by mass] (3)
[0080] In addition, the amount of the silane compound-containing composition adhering to the fiber structure relative to W0 was determined using the same procedure as above. This amount is referred to as the "adhering amount of the silane compound-containing composition before polymerization". Next, the fiber structure to which the silane compound-containing composition was attached was heat-treated at 180°C for 30 minutes. As a result, at least a part of the non-polymeric silane compound in the silane compound-containing composition adhering to the fiber structure was hydrolyzed and polymerized to generate a polymeric silane compound. Next, the fiber structure was immersed in water for 240 minutes, then pulled out of the water and dried at 80°C for 10 minutes, and its mass (W3) was measured. The amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to the mass (W0) of the fiber structure to which the silane compound-containing composition was not attached was determined using the following formula (4). Amount of the silane compound-containing composition attached to the fiber structure after polymerization and washing relative to W0 [parts by mass] = {(W3-W0) / W0} x 100 (4) If the fiber structure subjected to the heat treatment process still has non-polymeric silane compounds, the non-polymeric silane compounds are released from the fiber structure into water by immersing in water as described above.Therefore, the difference between "the amount of the silane compound-containing composition attached before polymerization" and "the amount of the silane compound-containing composition attached after polymerization and washing relative to W0" calculated according to formula (4) corresponds to the amount of non-polymeric silane compounds released from the fiber structure into water by washing with water after polymerization, and the smaller this value is, the more the hydrolysis and polymerization of the silane compounds attached to the fiber structure progresses, and the more polymeric silane compounds are produced. Since a reaction similar to the hydrolysis and polymerization is considered to occur with respect to non-polymeric silanes released from a fiber structure to which a silane compound-containing composition is attached and embedded in a hydraulic composition, the difference was calculated to confirm whether or not the cured body contains a polymeric silane compound.
[0081] <Measurement of the mass of hydrocarbons derived from alkyl groups eliminated from silane compounds> A hydraulic composition was prepared by adding different amounts of silane compounds to each of a number of mortars with W / C 50% by mass and a cement to fine aggregate mass ratio of 1:3. The mixture was mixed until it was homogenous. Each hydraulic composition was cast into a wooden formwork, and the casting surface together with the wooden formwork was wrapped and sealed. After 28 days, the seal was removed and the hardened body was obtained by leaving it in an environment of 20°C and 60% RH for 30 days or more. Samples were cut out from each of the obtained hardened bodies, and the amount of hydrocarbons derived from the alkyl group released from the silane compounds contained in the samples was measured by pyrolysis gas chromatography. Specifically, the cut out samples were crushed to a maximum dimension of 250 μm or less, 10 mg of the sample was set on a sample stand, and the chamber was replaced with nitrogen gas. Next, the temperature was raised from 60°C to a set temperature of 260°C at 10°C / min, held at 260°C for 8 minutes, and then cooled to 60°C. A mass spectrum was obtained for the hydrocarbon gas generated from the sample, and a calibration curve was prepared for the mass (g) of hydrocarbons derived from alkyl groups released from the silane compounds contained in the sample per 100 g of cement contained in the sample. For each of the cured bodies produced in the examples and comparative examples, a mass spectrum was obtained using pyrolysis gas chromatography in the same manner as above, except that the entire cured body was crushed instead of a sample cut out from the cured body. Also, for each of the other cured bodies produced in the examples and comparative examples, a mass spectrum was obtained using pyrolysis gas chromatography in the same manner as above, except that a sample was cut out from a region within 10 mm from the fiber structure and crushed. Using the obtained mass spectrum and the prepared calibration curve, the mass (g) of hydrocarbons derived from alkyl groups released from the silane compounds contained in the cured body per 100 g of cement in the entire hardened body, and the mass (g) of hydrocarbons derived from alkyl groups released from the silane compounds contained in the cured body per 100 g of cement contained in a piece of the cured body cut out from the cured body within a region 10 mm from the fiber structure were determined. Each measurement was carried out twice, and the average value was taken as the amount of hydrocarbon derived from the alkyl group eliminated from the silane compound. This alkyl group is an alkyl group possessed by a silane compound, i.e., an alkyl group derived from a silane compound. A large amount of alkyl group-derived hydrocarbons per 100 g of cement detected by pyrolysis gas chromatography mass spectrometry of a sample means that the sample contains a large amount of silane compounds. In addition, the analysis of alkyl group-derived hydrocarbons was performed on a hardened body, but since the amount of alkyl group and the amount of silane compound do not substantially change due to hardening of the hydraulic composition, the mass of alkyl group-derived hydrocarbons in the obtained hardened body can be considered to be equivalent to the mass of alkyl group-derived hydrocarbons in an unhardened body that has hardened to a certain extent.
[0082] <Distance between fiber structure and rebar> A piece of mortar near the reinforcing bar in the hardened body was split, and the distance between the reinforcing bar and the fiber structure closest to the reinforcing bar was measured at three arbitrary points. The average value was calculated, and this value was regarded as the distance between the fiber structure and the reinforcing bar in the hardened body. Since the distance between the fiber structure and the reinforcing bar does not substantially change due to the hardening of the hydraulic composition, the calculated distance between the fiber structure and the reinforcing bar in the hardened body can be regarded as the distance between the fiber structure and the reinforcing bar in the unhardened body.
[0083] <Water repellency or hydrophobicity of the hardened body> The water repellency or hydrophobicity of the cured bodies produced in the Examples and Comparative Examples was evaluated according to the following procedure. Water was sprayed onto the outer surface of the hardened body, near which the fiber structure was embedded (the surface that was in contact with the bottom surface of the formwork). The change in color of the exterior due to the sprayed water was visually observed to confirm whether water repellency or hydrophobicity was expressed.
[0084] [Example 1] <Production of fiber structures> A polyvinyl alcohol spun yarn (Cremona, average fiber diameter 15 μm) was immersed for 5 minutes in Protectosil (registered trademark) WA CIT (manufactured by Evonik Industries, silane compound concentration 50 mass%, containing alkylsilane monomers and an emulsion of alkylsilane oligomers having propoxy groups or propyl groups) as a silane compound-containing composition, and then pulled out, squeezed out, and dried at 80° C. for 10 minutes to produce a fiber structure having a silane compound-containing composition attached thereto. The amount of the silane compound-containing composition adhering to the fiber structure was 70 parts by mass relative to 100 parts by mass of the fiber structure to which the silane compound-containing composition was not attached. The amount of the silane compound released was 52 parts by mass, and the amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0 was 13 parts by mass. Therefore, the difference between the "amount of the silane compound-containing composition adhering before polymerization" and the "amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0" was 57 parts by mass. The produced fiber structure was cut to a desired length for use in preparing an uncured body.
[0085] <Production of Uncured and Cured Bodies> The reinforcing bar and the fiber structure manufactured by the above method were buried in mortar with a W / C of 50% by mass and a mass ratio of cement to fine aggregate of 1:3. Specifically, first, a wooden formwork with inner dimensions of 100 mm length x 200 mm width x 100 mm height was prepared, and one reinforcing bar with a length of 250 mm was fixed so that the reinforcing bar penetrated the wooden formwork. At this time, the reinforcing bar was fixed so that it was parallel to the long side direction of the wooden formwork, divided the length of the short side direction of the wooden formwork in half, and was horizontally arranged at a position where the bottom surface of the reinforcing bar was 10 mm from the inner bottom surface of the wooden formwork. Next, the above fiber structure (length 100 mm) was placed directly below the reinforcing bar so as to be in contact with the reinforcing bar, and both ends were fixed to the reinforcing bar with cable ties. At this time, both ends of the fiber structure were fixed to the reinforcing bar so that the midpoint of the reinforcing bar and the midpoint of the fiber structure were almost the same. Further, one of the above-mentioned fiber structures (length 120 mm) was placed directly below the fiber structure, perpendicular to the fiber structure, and bisect the length of the long side direction of the wooden formwork, at a position 10 mm from the inner bottom surface of the wooden formwork, and both ends were fixed to the formwork with a tacker. Two of the above-mentioned fiber structures were placed at 20 mm intervals on both sides of the fiber structure fixed with the tacker, at a position 10 mm from the inner bottom surface of the wooden formwork, and both ends were similarly fixed to the formwork with a tacker. Next, mortar was poured into the wooden formwork after being kneaded and left to stand until the bleeding water stopped rising, and the entire mixture was kneaded to be uniform, thereby producing an uncured body in which the fiber structure and the reinforcing bar were embedded in the hydraulic composition in this order from the surface of the uncured body (the surface of the uncured body in contact with the inner bottom surface of the wooden formwork) toward the inside. In the produced uncured body, the amount of the silane compound per 100 g of cement in a range within 10 mm from the fiber structure is greater than the amount of the silane compound per 100 g of cement in the entire uncured body. Next, the casting surface was wrapped and sealed together with the wooden formwork, and after 28 days, the seal was removed and the formwork was removed, and the hardened body was produced by leaving it in an environment of 20°C and 60% RH for 30 days or more. Then, the mortar pieces directly below the reinforcing bars were split and collected, and pulverized to a maximum dimension of 250 μm or less. In addition, the mortar pieces above the reinforcing bars and in the range of more than 0 mm to 10 mm from the fiber structure were split and collected, and pulverized to a maximum dimension of 250 μm or less. The obtained pulverized material was subjected to pyrolysis gas chromatography mass spectrometry to determine the mass of alkyl group-derived hydrocarbons per 100 g of cement within a range of 10 mm from the fiber structure. It was confirmed that the mass of alkyl group-derived hydrocarbons detected per 100 g of cement contained in the hardened body in the range of 10 mm from the fiber structure was equivalent to the amount of alkyl group-derived hydrocarbons detected when a hardened body of a hydraulic composition containing cement and 1.44 parts by mass of Protectosil (registered trademark) WA CIT per 100 parts by mass of the cement was subjected to pyrolysis gas chromatography mass spectrometry. Another hardened body was produced in the same manner as above, and the mortar pieces from the entire hardened body were pulverized, and the pulverized material was subjected to pyrolysis gas chromatography mass spectrometry to determine the mass of alkyl group-derived hydrocarbons per 100 g of cement in the entire hardened body. Since this mass was less than the mass of alkyl group-derived hydrocarbons per 100 g of cement within 10 mm from the above-mentioned fiber structure, it was confirmed that the amount of silane compound per 100 g of cement within 10 mm from the fiber structure embedded in the unhardened body was greater than the amount of silane compound per 100 g of cement in the entire unhardened body. The distance between the fiber structure and the rebar in the hardened body was 0 mm. Another hardened body was produced using the same procedure as above, and the water repellency or hydrophobicity of the hardened body was evaluated. At the location where the fiber structure was installed, there was little color change due to wetting, and it was observed that the water repellency or hydrophobic effect was exerted by the silane compound diffused from the fiber structure. In such a hardened body, the rust prevention effect for the reinforcing bar embedded in the hydraulic composition was also exerted.
[0086] [Examples 2 to 5] Fiber structures having a silane compound-containing composition attached thereto were produced and evaluated in the same manner as in Example 1, except that the concentration of Protectosil (registered trademark) WA CIT was adjusted so that the amount of the silane compound-containing composition attached to the fiber structure was 13 parts by mass, 25 parts by mass, 45 parts by mass, or 66 parts by mass relative to the mass of the fiber structure not having the silane compound-containing composition attached thereto. In each example, the amount of silane compound released was 4 parts by mass, 12 parts by mass, 27 parts by mass, or 47 parts by mass, and the amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0 was 5 parts by mass, 7 parts by mass, 11 parts by mass, or 13 parts by mass, respectively. Therefore, in each example, the difference between the "adhering amount of the silane compound-containing composition before polymerization" and the "amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0" was 8 parts by mass, 18 parts by mass, 34 parts by mass, or 53 parts by mass, respectively.
[0087] Cured products of each Example were produced and evaluated in the same manner as in Example 1, except that the fiber structure to which the silane compound-containing composition produced in each Example was adhered was used. It was confirmed that the amount of the silane compound per 100 g of cement in the range within 10 mm from the fiber structure was greater than the amount of the silane compound per 100 g of cement in the entire uncured body in all of Examples 2 to 5. It was also confirmed that the amount of the hydrocarbon derived from the alkyl group released from the silane compound contained in the cut piece of the hardened body, detected when the cut piece of the hardened body in the region within 10 mm from the fiber structure cut from the hardened body was subjected to pyrolysis gas chromatography mass spectrometry, was greater than the amount of the hydrocarbon derived from the alkyl group released from the silane compound contained in the hardened body, detected when the hardened body of the hydraulic composition containing cement and 0.5 parts by mass of the silane compound per 100 parts by mass of the cement was subjected to pyrolysis gas chromatography mass spectrometry. In all of Examples 2 to 5, the distance between the fiber structure and the reinforcing bar in the hardened body was 0 mm. In addition, in the area where the fiber structure was installed, when the amount of the silane compound-containing composition relative to W0 was 25 parts by mass or more (i.e., Examples 3 to 5), the color change due to wetting was small, and it was observed that the water-repellent or hydrophobic effect was expressed by the silane compound diffused from the fiber structure. In such a hardened body, the rust-preventive effect on the reinforcing bar embedded in the hydraulic composition is also expressed. When the amount of the silane compound-containing composition relative to W0 was 13 parts by mass (i.e., Example 2), the water-repellent or hydrophobic effect was confirmed to be expressed by the silane compound diffused from the fiber structure, but the degree was lower than in Examples 1 and 3 to 5. In Example 2, six long-fiber fiber structures were used, but it is considered that the water-repellent or hydrophobic effect expressed can be improved by, for example, increasing the number of fiber structures and narrowing the interval between the fiber structures.
[0088] [Example 6] A fiber structure having a silane compound-containing composition attached thereto was produced in the same manner as in Example 1, except that polyvinyl alcohol filaments (twisted yarn, average fiber diameter: 15 μm) were used instead of polyvinyl alcohol spun yarn (Cremona). The amount of the silane compound-containing composition adhering to the fiber structure was 73 parts by mass relative to the mass of the fiber structure to which the silane compound-containing composition was not attached. The amount of the silane compound released was 51 parts by mass, and the amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0 was 15 parts by mass. Therefore, the difference between the "amount of the silane compound-containing composition adhering before polymerization" and the "amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0" was 58 parts by mass. An uncured body and a cured body were produced and analyzed in the same manner as in Example 1, except that the produced fiber structure to which the silane compound-containing composition was attached was used. As can be seen from the fact that the uncured body was produced in the same manner as in Example 1, the amount of silane compound per 100 g of cement within 10 mm of the fiber structure in the produced uncured body was greater than the amount of silane compound per 100 g of cement in the entire uncured body. Also, the distance between the fiber structure and the reinforcing bar in the hardened body was 0 mm. In the evaluation of the water repellency or hydrophobicity of the hardened body, it was found that the color change due to wetting was small, and the water repellency or hydrophobicity effect was expressed by the silane compound diffused from the fiber structure. In such hardened body, the rust prevention effect for the reinforcing steel embedded in the hydraulic composition is also expressed.
[0089] [Example 7] A fiber structure having a silane compound-containing composition adhered thereto was produced in the same manner as in Example 1, except that drying at 30°C for 24 hours was performed instead of drying at 80°C for 10 minutes. The amount of the silane compound-containing composition adhering to the fiber structure was 53 parts by mass relative to the mass of the fiber structure to which the silane compound-containing composition was not attached. The amount of the silane compound released was 34 parts by mass, and the amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0 was 10 parts by mass. Therefore, the difference between the "adhering amount of the silane compound-containing composition before polymerization" and the "amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0" was 43 parts by mass.
[0090] [Example 8] A fiber structure having a silane compound-containing composition adhered thereto was produced in the same manner as in Example 1, except that Master Protect H400 (manufactured by Pozzolith Solutions, Inc., silane compound concentration 40 parts by mass, containing an alkylsilane monomer, and an emulsion of an alkylsilane oligomer having a propoxy group or a propyl group) was used instead of Protectosil (registered trademark) WA CIT. The amount of the silane compound-containing composition adhering to the fiber structure was 49 parts by mass relative to the mass of the fiber structure to which the silane compound-containing composition was not attached. The amount of the silane compound released was 23 parts by mass, and the amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0 was 20 parts by mass. Therefore, the difference between the "adhering amount of the silane compound-containing composition before polymerization" and the "amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0" was 29 parts by mass.
[0091] [Example 9] A fiber structure having a silane compound-containing composition attached thereto was produced in the same manner as in Example 1, except that a polyester braided cord (hydrophobic, the average fiber diameter of the fibers constituting the braided cord was 34 μm) was used instead of the polyvinyl alcohol spun yarn (Cremona). The amount of the silane compound-containing composition adhering to the fiber structure was 24 parts by mass relative to the mass of the fiber structure to which the silane compound-containing composition was not attached. The amount of the silane compound released was 11 parts by mass. The amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0 was 8 parts by mass. Therefore, the difference between the "amount of the silane compound-containing composition adhering before polymerization" and the "amount of the silane compound-containing composition adhering to the fiber structure after polymerization and washing relative to W0" was 16 parts by mass.
[0092] [Comparative Example 1] Protectosil (registered trademark) WA-CIT in an amount of 2 parts by mass per 100 parts by mass of cement was mixed with water to prepare mixing water. Using the prepared mixing water, mortar with a W / C ratio of 50% by mass and a cement to fine aggregate ratio of 1:3 was prepared. Next, a wooden form with inner dimensions of 100 mm length × 200 mm width × 100 mm height was prepared, and one reinforcing bar with a length of 250 mm was fixed so that the reinforcing bar penetrated the wooden form. At this time, the reinforcing bar was fixed so that it was parallel to the long side direction of the wooden form, divided the length of the short side direction of the wooden form in half, and was positioned horizontally with the bottom surface of the reinforcing bar 10 mm from the inner bottom surface of the wooden form. Next, the mortar was poured into the wooden formwork after being left to stand until the bleeding water stopped rising after mixing and remixing to make the entire mixture uniform. The casting surface of each wooden formwork was then sealed with plastic wrap, and after 28 days the seal was removed and the concrete was left in an environment of 20°C and 60% RH for at least 30 days to produce a hardened body. Mortar pieces directly below the rebar were split and collected, and pulverized to a maximum dimension of 250 μm or less. Mortar pieces above the rebar and in the range of more than 0 mm to 10 mm from the fiber structure were split and collected, and pulverized to a maximum dimension of 250 μm or less. The resulting pulverized material was subjected to pyrolysis gas chromatography mass spectrometry to determine the mass of alkyl group-derived hydrocarbons per 100 g of cement. It was confirmed that the mass of alkyl group-derived hydrocarbons detected per 100 g of cement contained in a hardened product of a hydraulic composition containing cement and 1.32 parts by mass of Protectosil (registered trademark) WA CIT per 100 parts by mass of the cement was equivalent to the amount of alkyl group-derived hydrocarbons detected per 100 g of cement contained in the hardened product when the hardened product was subjected to pyrolysis gas chromatography mass spectrometry. Another hardened body was produced using the same procedure as above, and the water repellency or hydrophobicity of the hardened body was evaluated. No color change due to wetting was observed, and the water repellency or hydrophobicity effect of the silane compound kneaded into the mortar was not expressed.
[0093] [Comparative Example 2] A heat-treated fiber structure was produced in the same manner as in Example 1, except that polyvinyl alcohol spun yarn (Cremona, average fiber diameter: 15 μm) dried at 80°C for 10 minutes was further heat-treated at 180°C for 30 minutes. The amount of the silane compound-containing composition contained in the fiber structure after the heat treatment was 24 parts by mass relative to the mass of the fiber structure to which the silane compound-containing composition was not attached. The amount of the released silane compound was 0.3 parts by mass. The fact that the amount of the released silane compound was significantly smaller than that of Example 1 indicates that the hydrolysis and polymerization of the silane compound attached to the fiber structure progressed due to the heat treatment, and a polymeric silane compound was generated. That is, in the fiber structure after the heat treatment, the composition containing the silane compound is fixed or set to the fiber structure and does not adhere. Note that the conditions of the heat treatment are sufficient for the hydrolysis and polymerization of the silane compound to progress, so the amount of the released silane compound is not the amount of the silane compound released from the fiber structure into the water, but the amount of a part of the polymeric silane compound that has fallen off from the fiber structure into the water due to a physical action. Even if an uncured body and a cured body are produced using such a fiber structure in the same manner as in Example 1, since the non-polymeric silane compound is not released from the fiber structure, it is not possible to obtain an uncured body containing a hydraulic composition and a fiber structure that will result in a cured body that exhibits water-repellent, hydrophobic and / or rust-proofing effects. [Explanation of symbols]
[0094] 1 Uncured body 2 Hydraulic composition 3. Fiber structure having silane compound-containing composition attached thereto 4. Steel Bars
Claims
1. The uncured body includes a hydraulic composition containing cement and a fiber structure having a composition containing a silane compound attached thereto, the fiber structure being embedded in the hydraulic composition.
2. The uncured body according to claim 1 , wherein the silane compound comprises a polymerizable silane compound.
3. 2. The uncured body according to claim 1, wherein the silane compound is one or more compounds selected from the group consisting of organosilanes and organosiloxanes.
4. The uncured article of claim 1 , wherein the silane compound comprises a monomeric silane compound.
5. 2. The uncured body according to claim 1, wherein the amount of the silane compound per 100 g of cement in a range within 10 mm from the fiber structure is greater than the amount of the silane compound per 100 g of cement in the entire uncured body.
6. The uncured body according to claim 1 , wherein the fibers constituting the fiber structure have no acidic or basic functional groups and have hydrophilic functional groups.
7. 2. The uncured body according to claim 1, wherein the fibers constituting the fiber structure are polyvinyl alcohol fibers.
8. 2. The uncured body according to claim 1, further comprising a reinforcing bar, the reinforcing bar being embedded in the hydraulic composition in the order of the fiber structure and the reinforcing bar from the surface of the uncured body toward the inside.
9. The uncured body according to claim 8 , wherein the distance between the fiber structure and the reinforcing bar is 10 mm or less.
10. 2. The uncured body according to claim 1, wherein the fiber structure is at least one selected from the group consisting of long fibers, woven fabrics, knitted fabrics, nonwoven fabrics, unidirectional fiber bundles, spun yarns, and braided cords.
11. A cured product of the uncured product according to claim 1.
12. The cured product of claim 11 comprising a polymeric silane compound.
13. The hardened body according to claim 11 or 12, wherein the silane compound has an alkyl group, and the amount of hydrocarbons derived from the alkyl group eliminated from the silane compound contained in the hardened body, detected when a cut piece of the hardened body cut out from a region within 10 mm from the fiber structure is subjected to pyrolysis-gas chromatography-mass spectrometry, per 100 g of cement contained in the cut piece of the hardened body is greater than the amount of hydrocarbons derived from the alkyl group eliminated from the silane compound contained in the hardened body, detected when a hardened body of a hydraulic composition comprising cement and 0.5 part by mass of the silane compound per 100 parts by mass of the cement is subjected to pyrolysis-gas chromatography-mass spectrometry, per 100 g of cement contained in the hardened body.
14. A fiber structure having a composition containing a silane compound attached thereto, the amount of the composition being 10 to 300 parts by mass per 100 parts by mass of the fiber structure to which the composition is not attached.
15. The fibrous structure of claim 14 , wherein the silane compound comprises a polymerizable silane compound.
16. The fibrous structure according to claim 14, wherein the silane compound is one or more compounds selected from the group consisting of organosilanes and organosiloxanes.
17. The fibrous structure of claim 14 , wherein the silane compound comprises a monomeric silane compound.
18. The fiber structure according to claim 14 , wherein the fibers constituting the fiber structure have no acidic or basic functional groups and have hydrophilic functional groups.
19. The fiber structure according to claim 14, wherein the fibers constituting the fiber structure are polyvinyl alcohol fibers.
20. The fiber structure according to claim 14, which is one or more selected from the group consisting of long fibers, woven fabrics, knitted fabrics, nonwoven fabrics, unidirectional fiber bundles, spun yarns, and braided cords.
21. The following formula: Silane compound release amount [mass parts] = Adhesion amount of silane compound-containing composition before cleaning [parts by mass] - Adhesion amount of silane compound-containing composition after cleaning [parts by mass] [In the formula, the adhesion amount of the silane compound-containing composition is the ratio of the mass of the silane compound-containing composition adhered to the fiber structure to 100 parts by mass of the fiber structure to which the silane compound-containing composition is not adhered] The fiber structure according to claim 14, wherein the amount of the silane compound released is 3 parts by mass or more.
Citation Information
Patent Citations
Synthetic fibre for reinforced concrete with rust prevention function and method for preparing same
CN101337782A
Oligomer mixture of n-propylethoxysiloxane, method for producing the same and use thereof
JP2002226490A
Dilution-stable aqueous compositions for the mass hydrophobization of mineral building materials
WO2022128994A1